Chronic migraine patients show cognitive impairment in an extended neuropsychological assessment - Karen S. Ferreira; Caroliny T. Teixeira; Carolina Cáfaro; Gabriela Z. Oliver; Gabriela L. P. Carvalho; Larissa A. S. D. Carvalho; Brenda G. Silva; Fernanda B. B. Haes; Marcelo C. Ciciarelli (Arquivos de Neuro-Psiquiatria)
ABSTRACT The objective of the present study was to assess the presence of cognitive deficits in patients with chronic migraine, and to assess the main factors that trigger cognitive disorders, such as comorbidities or the use of medications. Methods: Chronic migraine and control groups were interviewed in a case-control study. The frequency and intensity of the headache, medication used and associated comorbidities were determined. All patients were submitted to an extended neuropsychological assessment. Results: The chronic migraine group (n = 30) had a worse performance in the Montreal Cognitive Assessment Test (p = 0.00), Verbal Fluency (p = 0.00), Stroop (p = 0.00), Clock Drawing Test (p = 0.00), Digit Span (p = 0.00) and Matrix Reasoning (p = 0.01). After statistical adjustment by linear regression, migraine continued to be the only relevant factor in the poorer performance in the Montreal Cognitive Assessment, Verbal Fluency, Clock Drawing and Stroop tests. Conclusion: Patients with chronic migraine have cognitive deficits in multiple tasks, regardless of the presence of comorbidities or the use of medications.